A questão trabalhista em debate (1930-1937) - Pegoraro, Mônica Renata Schmidt (2022)
The thesis addresses the political, parliamentary, and legal debates surrounding the labor problem throughout the process of creating and organizing the Labor Court in Brazil. It aims to outline the evolution of labor justice since its creation in the 1934 Constitution until mid-1937, when the draft project of the Labor Court was analyzed by the Chamber of Deputies. The study is divided into four chapters, the first of which examines the parliamentary discourses on the labor problem contained in the Annals of the National Constituent Assembly (1933-1934). It explores the parliamentary performance of the proletarian representation, which, committed to opposing employer arbitrariness and police violence against union leaders, demanded that legislation consistent with workers' needs be drafted as soon as possible. The second and third chapters analyze parliamentary debates on labor issues and the Labor Court in the context of the provisional Chamber (1934-1935), and in setting of the ordinary Chamber of Deputies from the perspective of the Gazette of the Legislative Power (1934-1936), in the second and third chapter, respectively. The fourth chapter discusses the parliamentary debates in the Gazette of the Legislative Power for the year 1937, as well as the legal ramifications of the Labor Court in the Labor Magazine and the works: Problems of Corporate Law by Oliveira Viana, author of the draft of the Labor Court's organization, and Principles of Social Legislation and Procedural Labor Law by Waldemar Ferreira, rapporteur of the project.